Corynebacterium glutamicum promoters: a practical approach - Pátek, Miroslav; Holátko, Jiří; Busche, Tobias; Kalinowski, Jörn; Nešvera, Jan (Microbial biotechnology, 2013)
Transcription initiation is the key step in gene expression in bacteria, and it is therefore studied for both theoretical and practical reasons. Promoters, the traffic lights of transcription initiation, are used as construction elements in biotechnological efforts to coordinate 'green waves' in the metabolic pathways leading to the desired metabolites. Detailed analyses of Corynebacterium glutamicum promoters have already provided large amounts of data on their structures, regulatory mechanisms and practical capabilities in metabolic engineering. In this minireview the main aspects of promoter studies, the methods developed for their analysis and their practical use in C. glutamicum are discussed. These include definitions of the consensus sequences of the distinct promoter classes, promoter localization and characterization, activity measurements, the functions of transcriptional regulators and examples of practical uses of constitutive, inducible and modified promoters in biotechnology. The implications of the introduction of novel techniques, such as in vitro transcription and RNA sequencing, to C. glutamicum promoter studies are outlined.
Keywords: Base Sequence; Gene Expression Regulation, Bacterial; regulace genové exprese u bakterií; metabolické sítě a dráhy; biotechnologie; Consensus Sequence; Promoter Regions, Genetic; Biotechnology; Bacterial Proteins; Metabolic Networks and Pathways; genetická transkripce; bakteriální proteiny; Corynebacterium glutamicum; molekulární sekvence - údaje; Molecular Sequence Data; konsenzuální sekvence; promotorové oblasti (genetika); Transcription, Genetic; sekvence nukleotidů